Technetium-99m pertechnetate imaging in diagnosis of Meckel's diverticulum - Leonidas, John C. (1974)
Abdominal imaging after intravenous injection of (99m)Tc pertechnetate is a simple, safe, and noninvasive diagnostic procedure to show ectopic gastric mucosa, which is present in most cases of symptomatic Meckel's diverticulum. It was performed in 13 infants and children suspected of having a Meckel's diverticulum, mainly because of unexplained rectal bleeding. Two of the three proven Meckel's diverticula were correctly identified by scintiscanning, while meticulous contrast x-ray studies were negative in each case. It is concluded that abdominal imaging is useful in the pre-operative diagnosis of symptomatic Meckel's diverticulum.